Identification of Major QTLs Associated With First Pod Height and Candidate Gene Mining in Soybean - Jiang, Hongwei; Li, Yingying; Qin, Hongtao; Li, Yongliang; Qi, Huidong; Li, Candong; Wang, Nannan; Li, Ruichao; Zhao, Yuanyuan; Huang, Shiyu; Yu, Jingyao; Wang, Xinyu; et al. (Frontiers in Plant Science, 2018)
First pod height (FPH) is a quantitative trait in soybean [Glycine max (L.) Merr.] that affects mechanized harvesting. A compatible combination of the FPH and mechanized harvester is required to ensure that soybean is efficiently harvested. In this study, 147 recombinant inbred lines, which were derived from a cross between ‘Dongnong594’ and ‘Charleston’ over 8 years, were used to identify the major quantitative trait loci (QTLs) associated with FPH. Using a composite interval mapping method with WinQTLCart (ver. 2.5), 11 major QTLs were identified. They were distributed on five soybean chromosomes, and 90 pairs of QTLs showed significant epistatic associates with FPH. Of these, 3 were main QTL × main QTL interactions, and 12 were main QTL × non-main QTL interactions. A KEGG gene annotation of the 11 major QTL intervals, revealed 8 candidate genes related to plant growth, appearing in the pathways K14486 (auxin response factor 9), K14498 (serine/threonine-protein kinase) and K13946 (transmembrane amino acid transporter family protein), and 7 candidate genes had high expression levels in soybean stems. These results will aid in building a foundation for the fine mapping of QTLs related to FPH and marker-assisted selection for breeding in soybean.